JUAL BELI AKUN GAME ONLINE MOBILE LEGENDS BANG BANG - Nabila, Nabila; Sulaiman, Sofyan; Azis, Said Abdul (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Islam Indragiri, 2024)
This study examines the buying and selling of Mobile Legends: Bang Bang accounts from the perspective of maqashid sharia and Islamic rationality. With the rapid growth of technology, online gaming has become a popular form of entertainment across all age groups, offering potential income opportunities. The research aims to assess whether these transactions bring more benefits (maslahah) than harms (mudharat), conserve natural resources, and align with Islamic principles. A qualitative research approach was employed to explore the mechanisms behind these transactions. Data was gathered through observation, interviews, and documentation, ensuring a comprehensive understanding of the practice. The study highlights that, according to maqashid sharia, evaluating an action requires considering both its positive and negative aspects. For instance, while the trade of khamr is prohibited due to its greater harms relative to benefits, exceptions are allowed in emergency situations—such as using khamr for medicinal purposes in controlled quantities. Using this analogy, the research suggests that despite technological advancements that support online game account trading, the practice may be considered irrational if it contradicts the Islamic rationality axiom that demands products be halal, thayyib, and free from waste. Ultimately, the study underscores the importance of applying traditional Islamic ethical frameworks to modern digital economic activities, ensuring that progress in technology is balanced with adherence to core Islamic values.